Sistem Informasi Penjualan Daster Handmade Berbasis Multiplatform Menggunakan WhatsApp Gateway - Asyhadi, Ahmad; Naibaho, Ronald (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2021)
Duratu Jambi is a business unit that utilizes Instagram for sales activities. The product offered is a handmade negligee. Based on the analysis of the current system, the limitations of Duratu's system hamper the performance of the admin staff and require a system that can be used to manage all sales transactions, and generate reports. The system design is implemented based on progressive web applications that can run on multiplatform, and the system development is based on the waterfall method. The system testing method uses integrated testing. The results of this study are a new system to provide convenience in transacting and managing reports in Duratu Jambi